Brain activity during dual task gait and balance in aging and age-related neurodegenerative conditions: A systematic review - Kahya, Melike; Moon, Sanghee; Ranchet, Maud; Vukas, Rachel R.; Lyons, Kelly E.; Pahwa, Rajesh; Akinwuntan, Abiodun; Devos, Hannes (Experimental gerontology, 2019)
The aims of this systematic review were to investigate (1) real-time brain activity during DT gait and balance, (2) whether changes in brain activity correlate with changes in behavioral outcomes in older adults and people with age-related neurodegenerative conditions. PubMed, PsycINFO, and Web of Science were searched from 2009 to 2019 using the keywords dual task, brain activity, gait, balance, aging, neurodegeneration, and other related search terms. A total of 15 articles were included in this review. Functional near-infrared spectroscopy and electroencephalogram measures demonstrated that older adults had higher brain activity, particularly in the prefrontal cortex (PFC), compared to young adults during dual task gait and balance. Similar neurophysiological results were observed in people with age-related neurodegenerative conditions. Few studies demonstrated a relationship between increased brain activity and better behavioral outcomes. This systematic review supports the notion that aging and age-related neurodegenerative conditions are associated with neuronal network changes, resulting in increased brain activity specifically in the PFC. Further studies are warranted to assess the relationship between increased PFC activation during dual task gait and balance and behavioral outcomes to better optimize the rehabilitation interventions. •Older adults and people with age-related neurodegenerative conditions had increased brain activity during dual task gait and balance•With aging and/or neurodegeneration people are less efficient to perform dual task, therefore, recruit alternative neural resources•It is currently unclear which EEG metrics are most sensitive in detecting brain activity during dual task gait and balance•It is important to understand the relationship between brain activity during dual task gait and balance and behavioral outcomes•Understanding that relationship might help to better optimize the rehabilitation interventions